The method of finite cells for the analysis of terrain subsidence caused by tectonic movements or by subterrain exploitation (Archives of Mechanics - Test, 2007)
A simple numerical procedure for determining two- and three-dimensional field of displacements in the terrain subsidence caused by tectonic movements is proposed. The procedure is based on the concept of J. Litwiniszyn, who treated the gravity flow of a solid medium as a stochastic process. In this procedure, an imagined two-dimensional system of cells analogous to the Galton’s board is assumed. Theoretical considerations are supported by simple experimental simulations.